Factors Related to Chronic Energy Deficiency among Pregnant Women - Shinta Novelia; Rukmaini; Ema Annisa (KHD-Production, 2021)
Background: Chronic energy deficiency (CED) is a condition where the mother suffers from a chronic (chronic) calorie and protein deficiency (malnutrition) which results in health problems in women of reproductive age and in pregnant women (pregnant women). Objective: This study aims to determine the factors associated with chronic energy deficiency (CED) in pregnant women at the Gunung Kaler Public Health Center, Tangerang Regency in 2019. Methodology: This study used a cross-sectional design. The sampling technique used cluster sampling. The population was 286 people and the sample in this study was 167 people. The research instrument consisted of a questionnaire about knowledge of CED in pregnant women. Results: The results of this study indicate that there was a significant relationship between knowledge with p value = (0.06), history of disease with p value = (0.001), and parity with p value = (0.009) against Chronic Energy Deficiency (CED) in pregnant women, and there is no significant relationship between family income with a value of p = (0.482) and education with a value of p = (0.745) on Chronic Energy Deficiency (CED) in pregnant women. Conclusions and Suggestions: It is hoped that the Gunung Kaler Health Center will provide counseling related to CED with a variety of interesting methods. CED, Knowledge, Medical History, Parity, Education, Family Income